Fraktur Komunitif Angulus – Korpus Mandibula dengan Pemasangan Titanium Miniplate dan Srew: Laporan Kasus - Sitompul, Riston R.; Lumintang, Nico; Tandililing, Sherly (e-CliniC, 2024)
Abstract: Communitive fracture of the mandible is quite complicated to achieve good results with the use of titanium miniplates and screws. The challenges faced start from tips and tricks for placing non-rigid miniplate and screw fixation. There are two methods in performing mandibular communitive fracture surgery, namely closed reduction and open reduction. We reported a case of a 19-year-old male referred to Prof. Dr. R. Kandou Hospital, Manado, with open right mandible fracture. The patient was diagnosed with mild head injury, cerebral edema, skull base fracture, communitive fracture of mandibular angulus and corpus, non-displaced maxillary zygoma fracture, and palatal dental sagittal fracture. The patient underwent open reduction surgery with internal fixation using titanium miniplates and screws, and was re-evaluated in the first week after surgery up to three weeks after surgery. The patient's functional chewing and mouth opening were within normal limits. There were no complications such as infection or nerve lesions. In conclusion, communitive mandibular fracture using an open reduction technique with titanium miniplate and screw internal fixation gives satisfactory result. Keywords: communitive mandibular fracture; open reduction; dental occlusion   Abstrak: Fraktur komunitif mandibula merupakan kasus yang cukup rumit untuk mencapai hasil yang baik dengan penggunaan titanium miniplate dan screw. Tantangan yang dihadapi mulai dari tips dan trik penempatan fiksasi miniplate dan screw yang tidak rigid. Terdapat dua metode dalam melakukan operasi fraktur komunitif mandibula, yaitu reduksi tertutup dan reduksi terbuka. Kami melaporkan kasus seorang laki-laki 19 tahun dirujuk ke RSUP Prof. Dr. R. Kandou, Manado dengan patah tulang dagu kanan terbuka. Pasien didiagnosis dengan cedera kepala ringan, edema serebri, fraktur basis krani, fraktur angulus - korpus mandibula dekstra komunitif, fraktur zigoma pars maksilaris dekstra non-displaced, dan fraktur sagital dental palatal. Pasien dilakukan operasi reduksi terbuka dengan fiksasi internal. Evaluasi dilakukan pada minggu pertama paska operasi, hingga tiga minggu paska operasi. Didapatkan fungsional mengunyah dan membuka mulut pasien ini dalam batas normal, serta tidak didapatkan komplikasi seperti infeksi maupun lesi saraf. Simpulan kasus ini ialah fraktur mandibula komunitif dengan teknik reduksi terbuka dan fiksasi internal titanium miniplate dan screw memberikan hasil yang memuaskan. Kata kunci: fraktur mandibula komunitif; reduksi terbuka; oklusi dental